2010
DOI: 10.4314/ijbcs.v3i6.53152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human activities on diversity and abundance of insects in Akure Forest Reserve, Ondo State, Nigeria

Abstract: This study was carried out to assess the impacts of human activities on insect diversity and abundance in Akure Forest Reserve, Nigeria. Three land uses (fallow land, cocoa agroforest and unlogged forest) were selected for field work within the forest reserve. An hectare block was centrally demarcated in each of the land use types where insects collection and enumeration of trees species took place. 13,578 insects distributed among 30 families belonging to 15 orders were collected and identified and preserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…In the study, the larval crude fibre and ash content were found to be 8.70 % and 2.9 % respectively which is lower than edible aquatic insects reported by Shantibala et al (2014). 24 The crude fibre content of the insect in this study was quite high, compared to other edible insects reported by Adeduntan 2005, 1 Mbah & Elekima 2007. 18 The high crude fibre content in the insects could be due to the chitin normally found in insects.…”
Section: Resultscontrasting
confidence: 62%
“…In the study, the larval crude fibre and ash content were found to be 8.70 % and 2.9 % respectively which is lower than edible aquatic insects reported by Shantibala et al (2014). 24 The crude fibre content of the insect in this study was quite high, compared to other edible insects reported by Adeduntan 2005, 1 Mbah & Elekima 2007. 18 The high crude fibre content in the insects could be due to the chitin normally found in insects.…”
Section: Resultscontrasting
confidence: 62%
“…This result is in agreement with the finding of Adjaloo et al (2012), who reported higher species richness observed in heavily shaded area farms than in widely spaced farms with less canopy cover. Adeduntan (2009) stated that a particular area with physical complexity affects the diversity and abundance of insects. Therefore, higher species diversity observed in higher LUM index areas might be attributed to the more diverse landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Study Area: Akure Forest Reserve is situated between Aponmu and Obada communities in Akure South Local Government of Ondo State, Nigeria at latitudes 7 o 16Ꞌ 41.77 N and longitudes 5 o 2Ꞌ 2.01 E. The strict nature reserve (Queen's plots) as shown in (Fig. 1), is a part of the Reserve and was instituted in 1948, covering an area of about 32 hectares (Adeduntan, 2009); established with a view to preserving the genetic diversity of the forest ecosystem.…”
Section: Methodsmentioning
confidence: 99%